PENINGKATAN AKTIVITAS BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN MENGGUNAKANSTRATEGI INQUIRY DISCOVERY LEARNING PADA SISWA KELAS VI SD N MONGGANGSEWON BANTULYOGYAKARTA TAHUN AJARAN 2014/2015 - Sutrida Asriani; Al. Sugijanto (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract: The aim of this research was to improve the study activities on social study by using strategy inquiry discovery learning of students class VI SD Negeri Monggang Sewon Bantul Yogyakarta. The action hypothesis on this research was strategy inquiry discovery learning can improve study activities on social study of students class VI SD Negeri Monggang Sewon Bantul Yogyakarta. The subject of this research was 19 students of class VI SD Negeri Monggang Sewon Bantul Yogyakarta. The object of this research was students study activities on social study. The teqnique for data collect on this research by using observation and documentation teqnique. An analysis teqnique for data observation result to know increase students study activities. The result of this research showed that the use of strategy inquiry discovery learning can improve study activities on social study has increased by anincrease in the result average students study activities of 57,19 % in the pre action, in thefirst cycle improved with average 66,31 % and 78,94 % in the second cycle.Â Â